2018
DOI: 10.1016/j.mce.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity enhancement of human thyroid carcinoma cells by the inhibitors of histone deacetylase sodium butyrate and valproic acid

Abstract: Radiotherapy is one of the leading treatments for clinical cancer therapy. External beam radiotherapy has been proposed as an adjuvant treatment for patients bearing differentiated thyroid cancer refractory to conventional therapy. Our purpose was to study the combined effect of HDAC inhibitors (HDACi) and ionizing irradiation in thyroid cancer cell lines (Nthy-ori 3-1, WRO, TPC-1 and 8505c). HDACi radiosensitized thyroid cancer cells as evidenced by the reduction of survival fraction, whereas they had no effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…In our study, we found that FK228, a class I HDAC inhibitor, radiosensitized SCLC cells. A previous report showed that HDACi radiosensitized human thyroid cancer cell lines but not the normal thyroid follicular epithelial cells [29]. In line with the selectivity of HDACi for radiosensitizing cancer cells, we observed that FK228 sensitized radioresistant SCLC cells to radiation.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, we found that FK228, a class I HDAC inhibitor, radiosensitized SCLC cells. A previous report showed that HDACi radiosensitized human thyroid cancer cell lines but not the normal thyroid follicular epithelial cells [29]. In line with the selectivity of HDACi for radiosensitizing cancer cells, we observed that FK228 sensitized radioresistant SCLC cells to radiation.…”
Section: Discussionsupporting
confidence: 87%
“…The reason is that butyrate inhibits the proliferation of threedimensional colorectal cancer organoids and enhances the radiation-induced cell death in colorectal cancer organoids through FOXO3A.However, butyrate does not increase radiationinduced cell death after irradiation of normal organoids (Park et al, 2020). In vitro experimental studies proved that sodium butyrate and valproic acid can enhance the radiosensitivity of human thyroid cancer cells (Perona et al, 2018).…”
Section: Changes Of Scfas and Radiation-induced Intestinal Injurymentioning
confidence: 99%
“…This demonstrates the incapacity of cells to repair double strand break (DSB) following HDAC inhibition [68,69,70,71]. These observations can be explained by the capacity of HDACi to repress proteins such as Rad50, Ku70 and Ku80, implicated in DDR [71,72]. Others studies showed that TSA, vorinostat and abexinostat can repress BRCA1 (Breast Cancer 1) and RAD51 (Recombination Protein A) expressions [73,74] and thereby inhibit the homologous recombination and the non-homologous recombination end joining DDR mechanisms [70,74,75,76].…”
Section: Effect Of Histone Deacetylase Inhibitors On Tumor Cellsmentioning
confidence: 99%